Blennolide derivatives from the soil-derived fungus Trichoderma asperellum PSU-PSF14. Issue 39 (27th September 2018) - Maha, Athip; Phainuphong, Patima; Rukachaisirikul, Vatcharin; Saithong, Saowanit; Phongpaichit, Souwalak; Hadsadee, Sarinya; Jungsuttiwong, Siriporn; Preedanon, Sita; Sakayaroj, Jariya
Abstract: Three new blennolide derivatives, blennolides L-N (1 –3 ), together with five known metabolites were isolated from the soil-derived fungus Trichoderma asperellum PSU-PSF14. Their structures were determined by analysis of spectroscopic data. Their relative configurations were determined by analysis of NOEDIFF data and confirmed by X-ray crystallography for compound 1 whereas the absolute configurations were established by means of experimental and calculated TDDFT ECD data. Compound 1 displayed antifungal activity against Cryptococcus neoformans ATCC90112 and ATCC90113 flucytosine-resistant with the MIC values of 128 and 64 μg/mL, respectively, and was inactive against noncancerous Vero cell lines. Graphical abstract: Image 1